Positioning and localization of two-wavelength interferograms for wavefront reconstruction with volume holographic media - Barbosa, Eduardo Acedo [UNESP] (Optica Publishing Group, 2010)
This work studies both theoretically and experimentally the formation of the contour interference patterns generated by a twowavelength real-time holographic interferometer. The resulting contour interference fringes are due to the intersection of the measured surface with parallel, equally spaced planes of constant elevation. The theoretical analysis describes how the spatial frequency of the elevation planes, their angular position, and the localization of the fringes depend on parameters of the optical setup. A theoretical model for fringe localization is developed and confirmed by the experiments, showing a strong dependence of the interferogram position on the slope of the studied surface. Due to the thick Bi12TiO20 crystal employed as the storage medium the Bragg selectivity of the holographic readout is also considered. © 2010 Optical Society of America.